Determinants that influence job satisfaction among employees in Selia Selenggara Selatan Sdn. Bhd. in Melaka Tengah / Najihah Khairul Anuar and Illyani Nazirah Mohd Mohayaddin - Khairul Anuar, Najihah; Mohd Mohayaddin, Illyani Nazirah (Faculty of Business and Management, 2016)
The study aims to identify the determinants that influenced job satisfaction among employees in Selia Selenggara Selatan Sdn. Bhd. (SSSSB) in Melaka Tengah. The study was conducted in order to find out the significant relationship between the independent variables with the dependent variable. The dependent variable is job satisfaction of employees in SSSSB. The independent variables in this study are working environment, compensation and supervisor support. The results of the findings were interpreted using Reliability Test, Descriptive Statistics, Pearson’s Correlation Coefficient and Multiple Regression. The population of the study referred to 129 of all employees in SSSSB. From the population, the sample size that had been selected is 97 employees in SSSSB. Simple random sampling method has been used as sampling technique for the study. Questionnaire is the tool used by researcher in order collecting data for this research. Data has been analyzed through Statistical Package for Social Sciences (SPSS). Frequency analysis, Descriptive statistics, Correlation and Multiple Regression analysis has been applied to draw the results of the study. This is mainly to answer the research objectives. The findings of the study shown that there is a positive relationship between all independent variables and dependent variables which prove H1, H2 and H3 hypothesis are accepted. The results of the study is helpful for all the employees at SSSSB so that they can get better understanding about the relationship exist between working environment, compensation, supervisor support and job satisfaction as a result employees can improve and contribute more toward the organization.